PENGEMBANGAN VIDEO INTERAKTIF REGULASI EMOSI ANAK USIA (5-6) TAHUN DI KOTA PRABUMULIH - Hovina, Windri; Suningsih, Taruni Suningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an interactive video on emotion regulation for children aged 5-6 years in Prabumulih City as a response to the limited availability of engaging and developmentally appropriate learning media that support children’s social-emotional growth. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation, combined with Tessmer’s formative evaluation through expert review, one-to-one evaluation, and small group evaluation. The developed product features interactive activities, basic emotion recognition, breathing exercises, and simple situational responses tailored to early childhood characteristics. The validation results indicate that the media is highly valid, with material validation scoring 97% and media validation scoring 96%. The practicality test also shows excellent results, with an 88% score in the one-to-one evaluation and 93% in the small group evaluation, resulting in an average practicality score of 90%, categorized as highly practical. These findings demonstrate that the interactive video is easy to use, engaging, and effectively supports children in expressing, recognizing, understanding, and regulating their emotions. Thus, the interactive emotion regulation video is considered valid, practical, and suitable for use as instructional media to enhance social-emotional learning in early childhood education settings.